“Fenología y rendimiento de cinco accesiones de “sacha inchi” ( plukenetia volubilis L.) propagados por enraizamiento de estaquillas en la localidad de bello horizonte” - Cruz Veintemilla, Luis Miguel (2013)
The aim of the present research is to study the production cycle of 5 accesions of sacha inchi propagated by rooting cuttings, contributing with the researches on vegetative propagation and genetic breeding in this crop. The statistical design used was a RCBD with 3 blocks and 1 O plants per accesion in each block. The distance between plants was 3 x 3 meters. Vegetativa propagation accelerates the reproductiva cycle of sacha inchi, whereas vegetatively propagated accessions (Mishquiyacu y Pinto Recodo) started the harvest 154 days after transplantation while the witness, botanical propagated by seed started the harvest at 230 days after transplantation. The treatment Mishquiyacu presentad larger fruits and seeds and greater yield per plant and per hectare comparad to the rest of accessions propagated by rooting of cuttings. All accessions had an average of 4 seeds per capsule, with no significant differences between them. Vegetative propagation allow intraspecific hybridization followed by selection and propagation of superior clones of sacha inchi in the segregating population. Keywords: cuttings, sub irrigated chamber, reproductiva cycle, harvest.